Description of the immature stages of nine species of Veturius (Coleoptera: Passalidae) - Salazar-Niño, Karen; Serrão, José Eduardo (Zootaxa, 2015)
The third instar of Veturius aspina Kuwert, V. assimilis (Weber), V. simillimus Kuwert, V. sinuatocollis Kuwert, V. sinuatus (Eschscholtz), V. crassus (Smith), V. impressus Hincks (as well as pupal stage), V. negroensis Boucher, and the first instar of V. oberthuri (Hincks) (Coleoptera: Passalidae) are described for the first time based on specimens from Argentina, Brazil, and Colombia. The most distinctive characters for these species are the presence and distribution of primary setae and the position, number, and size of the teeth of the metathoracic legs. An evident difference in the number of micro-conical projections on the maxillary stipes and measurements of the pars stridens (mesocoxae) suggests that these characters are useful for species identification. We present an identification key to the species of known larval Veturius (13), representing the 17.6% of total species recognized into genus. Light micrographs and scanning electronic micrographs are included for detailed characters.